Dual Interleaved LLC Converter for High Power Applications and Wide Load Range - Frivaldsky, Michal; Morgos, Jan; Kanovsky, Andrej (Elektronika ir Elektrotechnika, 2019)
Dual interleaved LLC resonant converter with half bridge topology of main circuit characterized by high switching frequency (500 kHz), high power density (60 W/inch3) and high efficiency (above 96 %) over entire operational range (20 %–100 %) is described. Focus was given on the practical design of power converter, which will be able to fulfil requirements on wide load range operation characterized by upcoming normative. Since proposed topology is based on dual interleaved LLC converter, the resonant component´s critical tolerance was also investigated to secure reliable and optimal operational point. Consequently, proposals for elimination of intolerance negative impact are also described. The results of theoretical analysis were verified directly through experimental measurements. Experimental results are finally compared with upcoming industrial standard 80 Plus Titanium.